#TITLE_ALTERNATIVE# - WIBOWO (NIM:26912320), AJITOMO
Austroads 2011 mechanistic procedure method is a method that uses an analytical approach. Austroads 2011 mechanistic method uses multilayers structural modeling that the calculations based on stress, strain and deformation due to the existing load. Determining the stress and strain of a pavement structure must be known the value of the Modulus of Elasticity (E) and Poisson Ratio 􀀋􀈝􀀌􀀃􀁒􀁉􀀃􀁈􀁄􀁆􀁋􀀃layer. The value of the Modulus of Elasticity (E) and Poisson Ratio 􀀋􀈝􀀌􀀃􀁆􀁄n be determined by deflection measurement. With analytical approach, Austroads 2011 mechanistic method can describe the real condition of the pavement. Bina Marga 2013 structural evaluation method also uses analytical methods with some climatic conditions and loading adjustment for Indonesia. The aim of this research is analysing of pavement structural condition based on the deflection data by Falling Weight deflectometer (FWD) measurement on Pantura National Road Palimanan-Cirebon segment and National Road Bandung-Purwakarta segment. The result of this research showed that From the Austroads 2011 methods using General Mechanistic Procedure (GMP) with CIRCLY program result by using 4 layers modeling, Palimanan- Cirebon segment require added 40-60 mm AC-WC overlay layer for 5-year design life, Bandung-Purwakarta segment require added 40 mm AC-WC overlay layer for 5-year design life. The Bina Marga 2013 method result Palimanan- Cirebon segment require added 60 mm AC-WC overlay layer for 5-year design life. Using chart by Bina Marga 2013 Manual Bandung-Purwakarta segment require added 90 mm AC-WC overlay layer for 5-year design life. It can be concluded both Austroads 2011 method and Bina Marga 2013 method use mechanistic methods to analyze structural evaluation. Bina Marga 2013 method uses mechanistic methods with some climatic conditions and loading adjustment that occurred in Indonesia.